Occurrence and Antimicrobial Resistance Profiles of MRSA and ESBL-Producing Enterobacteriaceae in a Veterinary Hospital Environment - Dameanti, Fidi Nur Aini Eka Puji; Effendi, Mustofa Helmi; Amri, Indah Amalia; Adrenalin, Sruti Listra; Luthfiana, Nurul; Syah, Ali Akram (Universitas Airlangga, 2025)
Background: Nosocomial infections pose a major challenge not only in human hospitals but also in veterinary settings. These infections are frequently associated with methicillin-resistant Staphylococcus aureus (MRSA) and extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-E). Purpose: This study aimed to detect and characterize MRSA and ESBL-E isolated from environmental samples at the Veterinary Teaching Hospital, Universitas Brawijaya (VTH UB). Method: The study involved four main procedures: (1) sample isolation; (2) bacterial identification of S. aureus and Enterobacteriaceae using MacConkey agar supplemented with 1 mg/L cefotaxime (MCA + 1 mg/L); (3) antibiotic susceptibility testing and MRSA confirmation using Oxacillin Resistance Screening Agar Base (ORSAB); and (4) confirmation of ESBL production through the Double Disk Synergy Test (DDST). Results: Isolation and identification revealed S. aureus in 86.6% (13/15) of samples and Enterobacteriaceae in 26.6% (4/15). Among Enterobacteriaceae, Klebsiella pneumoniae accounted for 6.7% (1/15) and Enterobacter aerogenes for 20% (3/15). Antimicrobial resistance testing of Staphylococcus aureus isolates showed that all (13/13) were resistant to at least one antibiotic class. Resistance rates were 53.8% (7/13) to oxacillin, 92.3% (12/13) to cefoxitin, 23.0% (3/13) to tetracycline, 92.3% (12/13) to erythromycin, and 46.1% (6/13) to gentamicin. The prevalence of MRSA among environmental isolates was 46.6% (7/15), while ESBL-E prevalence was 26.6% (4/15). Conclusion: The detection of MRSA and ESBL-E in the hospital environment indicates potential zoonotic and hospital associated infection risks in veterinary facilities. These findings emphasize the importance of strengthened infection control practices and provide a baseline for broader surveillance across veterinary hospitals.